TERRA SIGILLATA FROM THE VICUS AT KONTICH (PROV. ANTWERP, BELGIUM) - Thoen, Hugo; Verbeeck, Henri (Rei Cretariae Romanae Fautorum Acta, 2024)
Kontich is situated between two major cities, Antwerp and Mechelen, and can boast of a rich historical past. Excavations by the Antwerp Society for Roman Archaeology (AVRA) and the Institute for the Archaeological Heritage of the Flemish Community (IAP, now VIOE) have brought to light several rural settlements situated upon and around the 23,5 m high Alfsberg from the Middle Iron Age onwards, and a possibly Late Iron Age Celtic fanum some 800 m to the north.